2020
DOI: 10.3390/ijerph17176169
|View full text |Cite
|
Sign up to set email alerts
|

Working Alliance Inventory for Online Interventions-Short Form (WAI-TECH-SF): The Role of the Therapeutic Alliance between Patient and Online Program in Therapeutic Outcomes

Abstract: Background: Therapeutic alliance (TA) between the patient and therapist has been related to positive therapeutic outcomes. Because Internet-based interventions are increasingly being implemented, a tool is needed to measure the TA with Internet-based self-guided programs. The Working Alliance Inventory for online interventions (WAI-TECH-SF) was adapted based on the WAI Short Form (Hatcher & Gillaspy, 2006). The objectives of this study were: (1) to analyse the psychometric properties of the WAI-TECH-SF; (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
3
33
0
3
Order By: Relevance
“…Taken together, these findings suggest that the extent to which these and other variables predict patient and therapist involvement in iCBT requires further investigation. Along the same lines, the lack of relationship between guidance and outcomes in this study might be partly accounted for by the bond between the online platform and the patient, in other words, the participants' therapeutic alliance with the online program ( Herrero et al, 2020 ). Research has shown that, as in face-to-face psychotherapy, patients in Internet-delivered interventions are able to develop a bond with the online program ( Berry et al, 2018 ), and this relationship is positively associated with treatment outcomes and satisfaction with the treatment ( Gómez-Penedo et al, 2020 ; Pihlaja et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, these findings suggest that the extent to which these and other variables predict patient and therapist involvement in iCBT requires further investigation. Along the same lines, the lack of relationship between guidance and outcomes in this study might be partly accounted for by the bond between the online platform and the patient, in other words, the participants' therapeutic alliance with the online program ( Herrero et al, 2020 ). Research has shown that, as in face-to-face psychotherapy, patients in Internet-delivered interventions are able to develop a bond with the online program ( Berry et al, 2018 ), and this relationship is positively associated with treatment outcomes and satisfaction with the treatment ( Gómez-Penedo et al, 2020 ; Pihlaja et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…The remaining five studies cover different aspects related to ICTs. Considering the association between therapeutic alliance to treatment outcomes in psychotherapy and the increased use of internet-based interventions, Herrero et al [ 14 ] adapted The Working Alliance Inventory for online interventions (WAI-TECH-SF), based on the WAI Short Form [ 15 ]. Authors found good psychometric properties of the WAI-TECH-SF and its association with positive therapeutic outcomes (changes in depressive symptoms) and satisfaction with the treatment in a sample of 193 participants with depressed diagnosis.…”
mentioning
confidence: 99%
“…In this context, various ICT-based approaches and innovations have been introduced addressing the support of older adults' care (Padilla-Góngora and Padilla-Clemente, 2008) and ensuring many advantages related to increased accessibility and flexibility, promotion of empowerment and increase of innovation (Lal and Adair, 2014). Among others, these services can be categorized as technological aids and ambient assistedliving systems providing support to older adults in certain daily life activities; cognitive assessment or cognitive interventions based on ICT providing cognitive and emotional support for older adults and their caregivers (Barnes et al, 2009;Franco-Martín et al, 2011;Donker et al, 2013;García Lizana, 2013;Boots et al, 2014;Lampit A.H. et al, 2014;Xavier et al, 2014;Kauppi et al, 2015;Chan et al, 2016;Chen, 2016;World Health Organization (WHO), 2016;Herrero et al, 2020); and technologies and interventions aiming to enhance older people's social participation through technology (Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, technology-based interventions, i.e., interventions based on access and use of a technological device (e.g., computer, telephone) or process (e.g., internet, video), can potentially improve mental health and well-being of the older population, including those suffering from poor mental health (World Health Organization (WHO), 2016). Changes in depressive symptoms and satisfaction with the treatment were reported in a study implemented web-based interventions in a sample of 193 participants with depressed diagnosis (Herrero et al, 2020), while a more systematic review of eight studies exploring the use of mobile applications focusing on depression, anxiety disorders and substance abuse care found that apps have the potential to improve health outcomes and treatment accessibility (Donker et al, 2013). Furthermore, additional research has supported that access and interaction with electronic devices and telehealth services can help people suffering from mental health issues to manage and track their health indicators anywhere in the community (Kauppi et al, 2015), as well as maintain and enhance cognitive function (Chan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%